2007
DOI: 10.1186/gb-2007-8-5-r93
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and clinical validation of a pathogen detection microarray

Abstract: Pathogen detection by microarray

New design and optimization of pathogen detection microarrays is shown to allow robust and accurate detection of a range of pathogens. The customized microarray platform includes a method for reducing PCR bias during DNA amplification.

Abstract DNA microarrays used as 'genomic sensors' have great potential in clinical diagnostics. Biases inherent in random PCR-amplification, cross-hybridization effects, and inadequate microarray analysis, however, limit detection sensiti…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 42 publications
5
49
0
2
Order By: Relevance
“…In prior work, we have found that the length of longest perfect match (PM) is a strong predictor of hybridization intensity, and that for probes at least 50 nt long, PM≤20 bp have signal less than 20% of that with a perfect match over the entire length of the probe (2). This is similar to results from a systematic study of viral probe hybridization characteristics by (3). Therefore, for each target family we eliminated regions with perfect matches to sequences outside the target family.…”
Section: Sequence Analysis and Microarray Probe Design To Develop "Cesupporting
confidence: 77%
“…In prior work, we have found that the length of longest perfect match (PM) is a strong predictor of hybridization intensity, and that for probes at least 50 nt long, PM≤20 bp have signal less than 20% of that with a perfect match over the entire length of the probe (2). This is similar to results from a systematic study of viral probe hybridization characteristics by (3). Therefore, for each target family we eliminated regions with perfect matches to sequences outside the target family.…”
Section: Sequence Analysis and Microarray Probe Design To Develop "Cesupporting
confidence: 77%
“…Nucleic acid samples were reverse transcribed to cDNA using tagged random primers as described above (36), except that primer A2 (5Ј-GATGAGGGAAGATGGGGNNNNNNNNN-3Ј) was used (39). The cDNA was synthesized into double-stranded cDNA and then amplified by random PCR using primer B2 (5Ј-GATGAGGGAAGATGGGG-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analysis has the capability to offer multiplex detection, Multiple microarray platforms exist, including printed double-stranded DNA and oligonucleotide arrays, in situsynthesized arrays, high-density bead arrays, electronic microarrays, and suspension bead arrays (Wong et al, 2007). In general terms, probes are synthesized and immobilized as discrete features, or spots.…”
Section: Microarraysmentioning
confidence: 99%